EFEKTIVITAS HUKUMAN PENJARA BAGI PENYALAHGUNAAN NARKOTIKA SESUAI DENGAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Deni Saputro (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT With the issuance of Law Number  35 of 2009 concerning Narcotics in which legal sanctions are regulated, as well as the things that are allowed with the issuance of the law, the investigators are expected to be able to assist the process of settling cases against one or more people who have committed drug crimes today. And one of those sanctions is prison. Prison Crime is a punishment in the form of a limitation of freedom of movement of a convicted person by closing the person in a place called Lapas (Lapas), by requiring people to obey all the rules and regulations that apply in the relevant Prison. As is well known, national development in Indonesia has the aim of creating a just and prosperous society, which is materially and spiritually evenly based on the Pancasila and the 1945 Constitution.Based on the results of the description of the reasons for the selection of the title above, the writer wants to explore some of the problems that are made objects in writing this thesis are: 1). What is the community's role in dealing with obstacles in tackling narcotics distribution and abuse? 2). What is the Effectiveness of Prison Sentences for Narcotics Abuse in Accordance with Law Number 35 Year 2009?So it can be concluded as follows: 1). The Role of the Community in Preventing Narcotics Crimes in Samarinda. Related to narcotics prevention in Samarinda, there are several steps that must be taken so that prevention can proceed with effectiveness. In addition there are several important aspects that must be considered so that the level of effectiveness of prevention works well, including the following: (a). The role of elements of society (b). Coordination of individuals with elements of society (c). The role of society itself. 2). The application of imprisonment for narcotics abuse offenders has not been effective so far so that there is a need for a serious program to suppress the dependency of a narcotics abuse user or narcotics user. Not only that the collaboration between the Penitentiary with the BNN has never been held. Keywords: Prison Punishment, Narcotics Abuse